Analisis Manajemen Risiko Aplikasi DAPODIK Menggunakan COBIT 4.1 - Wardhani Pinarsere Silalahi; Resad Setyadi (STMIK Budi Darma, 2022)
In today's life, the role of technology is one of the important things in human life. technology in various fields that are very supportive, especially advances in the world of education. As in the use of DAPODIK (Education Principal Data) which has been implemented in all schools, one of which is at SMK N 1 Balige. The DAPODIK application is an application that can help staff, teachers, and students in reporting education data directly to the ministry online. In its implementation, technology is also inseparable from risks that may occur so that it can hamper business processes. The risk of problems in the DAPODIK application is an error when entering data. This study aims to analyze risk management in the DAPODIK application at SMK N 1 Balige which refers to COBIT (Control Objectives for Information and Technology) 4.1 PO (Plan and Organize) domain 9. The research method uses quantitative methods. With the distribution questionnaire, this activity becomes a measuring method for obtaining data, which will later be tested for validity and reliability, and can ensure the alignment of information technology with business management through calculating the level of maturity. The results of this study indicate that the maturity level of the DAPODIK application at SMK N 1 Balige is 2,5264, at level 3, which means the value is in the define process position. The recommendation from this research is the need for user training in the use of the DAPODIK application.